SYSTEM DESIGN OF DOMESTIC STEEL PRODUCTS SALES PREDICTION - Francisca L. Paath; Drs. Soetirto Sadikin, MA (Jurnal Sistem Informasi, 1995)
Various attempts were made to achieve these objectives, such as personnel planning, production, finance, equipment and marketing. A leader of the company is specifically responsible for the marketing needs of those who organized the ata from marketing research to make decisions that are associated with increased sales or to establish marketing strategies. To achieve these objectives, forecasts sales that are part of the marketing research is important because it can provide a snapshot of sales capabilities in the future. In terms of information technology is being developed at this time, data processing using computer technology will be helpful so that a quantitative data processing to guarantee the ease, speed and accuracy.